Fate of the Gas-Phase Reaction Between Oxirane and the CN Radical in Interstellar Conditions - Alessandrini, Silvia; Melosso, Mattia (Frontiers in Astronomy and Space Sciences, 2021)
The escalating identification of new complex molecules in the interstellar medium claims for potential formation routes of such species. In this regard, the present work considers the reaction between oxirane and the CN radical as a feasible formation mechanism of species having the C3H3NO molecular formula. Indeed, the compounds of this family are elusive in the interstellar medium and suggestions on which species could be formed at low temperature and low pressure conditions might aid their discovery. The c-C2H4O + CN reaction has been investigated from the thermodynamic and kinetic points of view. The thermodynamics has been studied by means of a double-hybrid density functional and revealed the presence of several mechanisms submerged with respect to the reactants energy, with the potential formation of oxazole and cyanoacetaldehyde. However, the kinetic results suggest that the main reaction pathway is the H-extraction, leading to 2-oxiranyl radical and HCN. The formation of cyanoacetaldehyde + H and of H2CCN + H2CO is also possible with smaller rate constants, while the production of oxazole is negligible due to the presence of a high energy barrier.